IMPROVEMENT OF TEACHER PERFORMANCE THROUGH THE IMPLEMENTATION OF A REWARD AND MOTIVATION SYSTEM IN NABIGH ACADEMIC SOPPENG EARLY CHILDHOOD EDUCATION - Fadli, Zul (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
This research delves into the implementation of the reward and motivation system to enhance the performance of teachers in early childhood education (PAUD) at Nabigh Academic Soppeng. The research findings reveal that despite the implementation of the system, significant challenges related to the uncertainty of reward criteria and a lack of teacher participation persist. Teachers express the desire for more involvement in determining criteria and personalized recognition. The impact of this system varies, with some teachers reporting increased motivation and performance, while others perceive less significant effects. Motivational and performance factors involve not only the reward system but also leadership support and the work environment. The gap between ideal expectations and implementation reality opens opportunities for improvement, emphasizing the need for revised reward criteria and increased transparency. Recommendations involve enhancing teacher participation in system design and integrating broader motivational factors. The implications of these findings provide a foundation for Nabigh Academic Soppeng PAUD to improve the effectiveness of the motivation system and the potential enhancement of teacher performance. In conclusion, this research contributes to the literature on PAUD motivation management, highlighting the importance of continuous improvement to achieve a system more tailored to teachers' needs and the goals of early childhood education.